2014
DOI: 10.1186/1471-2164-15-765
|View full text |Cite
|
Sign up to set email alerts
|

Liver transcriptome analysis in gilthead sea bream upon exposure to low temperature

Abstract: BackgroundWater temperature greatly influences the physiology and behaviour of teleost fish as other aquatic organisms. While fish are able to cope with seasonal temperature variations, thermal excursions outside their normal thermal range might exceed their ability to respond leading to severe diseases and death.Profound differences exist in thermal tolerance across fish species living in the same geographical areas, promoting for investigating the molecular mechanisms involved in susceptibility and resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 51 publications
5
52
0
Order By: Relevance
“…Severe cold weather often resulted in mass mortality of commercially important cultured species such as tilapia (Oreochromis niloticus) (Zerai et al, 2010), orange-spotted grouper (Epinephelus coioides) (Qi et al, 2013) and gilthead sea bream (Sparus aurata) (Mininni et al, 2014). It was reported that maintenance of cell membrane fluidity was an effective way to adapt to cold stress for fishes (Hsieh and Kuo, 2005;Hazel, 1979;Bell et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Severe cold weather often resulted in mass mortality of commercially important cultured species such as tilapia (Oreochromis niloticus) (Zerai et al, 2010), orange-spotted grouper (Epinephelus coioides) (Qi et al, 2013) and gilthead sea bream (Sparus aurata) (Mininni et al, 2014). It was reported that maintenance of cell membrane fluidity was an effective way to adapt to cold stress for fishes (Hsieh and Kuo, 2005;Hazel, 1979;Bell et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…; Mininni et al . ), and a transgenic zebrafish ( Danio rerio ) strain expressing carp muscle‐specific form III of creatine kinase showed enhanced cold resistance (Wang et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms related to cold adaptation in fish have been reported, including the alteration of cell-membrane fluidity (Johnston & Roots, 1964), recruitment of different muscle fibres (Gerlach et al 1990), synthesis of molecular chaperones (Fader et al 1994;Donaldson et al 2008), and generation of antifreeze proteins in freezing environments (Devries, 1971;Cao et al 2016). Moreover, several transcriptomic studies have indicated that numerous genes involved in energy metabolism are changed significantly in several fishes under cold stress (Gracey et al 2004;Mininni et al 2014), and a transgenic zebrafish (Danio rerio) strain expressing carp muscle-specific form III of creatine kinase showed enhanced cold resistance . The results of these studies suggest that energy metabolism correlates with cold resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the gilthead sea bream liver transcriptome revealed immediate and sustained activation of NFE2L2/NRF2, the main antioxidant response transcription factor, under cold stress (Mininni et al, 2014). The gene expression of antioxidant enzymes (SOD, GPx, and Cat) was also up-regulated upon acute hypothermal challenge in zebrafish livers (Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, changes in environmental salinities were found to be associated with the enhancement of ROS generation, whereas imbalance of the antioxidant mechanisms induced oxidative damage in aquatic organisms (Martínez-Alvarez et al, 2002; Paital and Chainy, 2010; Lushchak, 2011). Acute up-regulation of both enzymatic and non-enzymatic antioxidant mechanisms were reported in fish to neutralize ROS damage against the oxidative stress (Mininni et al, 2014; Nakano et al, 2014; Wu et al, 2015). Therefore, salinity and hypothermal stress together might enhance ROS generation and induce oxidative damage in FW low-temperature milkfish, leading to more acute up-regulation of prdx6 in the FW group (24 h) than the SW group (96 h) upon hypothermal challenge.…”
Section: Discussionmentioning
confidence: 99%